Household Drinking Water Testing for Public and Private Water Supplies - Yilin Zhuang; Andrea Albertin; Arthur G. Hornsby (EDIS, 2023)
Drinking water comes from a variety of sources including public water systems, private wells, or bottled water. While public water systems are monitored under the federal Safe Drinking Water Act, private wells are not regulated. Private well users are responsible for the management and protection of their wells.